Grant writing for medical and healthcare professionals - Parija, Subhash Chandra; Kate, Vikram (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
Conducting research requires resources to meet the research need. The resources in the research institutes/ centers are often inadequate, limiting the research outcome. Research grants help overcome those limitations and help the researchers carry out quality research without any restriction. Grant proposal writing is an essential skill to be mastered by every researcher. However, the majority of the medical schools, except the few research institutes, do not have a structured learning module for obtaining grants. On most occasions, the skill of writing grant proposals goes by self-learning. For students, it is burdening due to the tremendous time consumed to learn the craft of writing the grant proposal and the exhausting clinical and academic work. This book is carefully prepared to keep in mind the difficulties faced by the young researchers and the students concerning choosing a funding agency, grant makers' expectations, budgeting, surveillance and site visits,rights of the researcher and the funding agency, and ethical and legal aspects of obtaining the grant. The book also covers the alternate plan for partial funding or interruption of the financing, reporting the source of funding and acknowledgment, good clinical practice guidelines, and dealing with the rejected grant proposal. The research projects are often dropped or modified extensively due to the limited resources in the existing facility. The researchers are forced to compromise the research objective due to expensive requirements. There is a shortage of awareness regarding the availability of funding and grant for the conduct of research. Even if the researchers are aware of obtaining the financing, there is a lack of training in grant proposal writing, which is essential in getting the research funding. This book on grant proposal writing for medical and healthcare professionals covers such difficulties and deficiencies. It will provide complete companionship from knowing the funding agency to obtaining the grant. .
Section I: Understanding Grant Writing: What is your Aim (Ambition-Interest-Mission), and what you want to do -- What is a grant? How to prepare for writing a grant proposal application -- Funders Perspective: What the funding body expects from researchers? -- Funding organizations for science and healthcare -- Obtaining letters of support -- Section II: The process for grant writing: Writing a Grant Proposal for a Single Centre Study: step-by-step approach -- Budgeting the project-detailing the required funding and expenditure -- Proving the competency of the researcher and the adequacy of the infrastructure to carry out the research -- Agreement and MOU - ethical and legal aspects of funding for healthcare research -- Write an impressive cover page (Covering letter) and abstract for the grant proposal application -- Surveillance plan and site visit - Roles and rights of the researcher and the funding agency -- Sources of funding and acknowledgment - Good Clinical Practice Guidelines -- Writing agrant proposal for a Collaborative study -- Checklist for grant proposal - Mandatory elements -- Tips for improvising the chance of getting the grant -- Dealing with The Rejected Grant Proposal- Learning From The Mistakes -- Section III: Grant writing for specific regional funding organizations: Preparing a grant proposal for medical research in the UK -- Preparing a grant proposal for the USA -- Preparing a Grant Proposal for Australia -- Proposal Writing for Grant Application in Malaysia -- Grant writing for other Asian countries.
Keywords: Medicine -- Research; Biology -- Research; Research -- Methodology; Clinical medicine -- Research; Biomedical Research; Research Skills; Clinical Research